Pond & river - Parker, Steve, 1952-; Dowell, Philip (New York : Distributed by Random House, 1988)
A photo essay about the range of plants and animals found in fresh water throughout the year, examining the living conditions and survival mechanisms of creatures dwelling at the edge of the water, on its surface, or under the mud.
"A Dorling Kindersley book"--T.p. verso.
Includes index.
Elem. School Library Collection.
School Library Journal.
Wilson's Children.
Book Links (A.L.A.), June 1996.
Keywords: Pond ecology -- Juvenile literature; Stream ecology -- Juvenile literature; Ecology; Pond ecology; Stream ecology; Ecology; Pond ecology; Stream ecology